Blood TCTP as a potential biomarker associated with immunosuppressive features and poor clinical outcomes in metastatic gastric cancer - Changhoon Yoo; Hyung-Don Kim; Min-Hee Ryu; Yeong Hak Bang; Jiae Kim; Won-Tae Kim; Hayoung Lee; Hideyuki Yanai; Gwanghee Lee; Hee Jeong Kim; Seyoung Jung; Hyung Eun Lee; et al. (Journal for ImmunoTherapy of Cancer)
Background No established biomarker exists for specific myeloid cell populations or in gastric cancer. This study aimed to explore the prognostic and immunological relevance of plasma translationally controlled tumor protein (TCTP) in patients with advanced gastric cancer treated with an immune checkpoint inhibitor and/or cytotoxic chemotherapy.Methods Plasma samples were prospectively collected from the cohorts of patients with gastric cancer treated with first-line fluoropyrimidine plus platinum chemotherapy (n=143, cohort 1) and third-line nivolumab (n=165, cohort 2). Plasma TCTP levels were quantified using ELISA, and multiplex proteomic analysis (Olink) was conducted to assess expression levels of immune-related proteins. External single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics datasets were employed to validate the findings.Results Patients with high plasma TCTP levels (TCTP-high group) exhibited poor progression-free survival (PFS) and overall survival (OS) with first-line chemotherapy compared with those with low levels (TCTP-low group) in cohort 1 (HR: 1.73 for PFS; 1.77 for OS). In the TCTP-high group, proteins associated with immunosuppressive myeloid cells, angiogenesis, and immune exclusion of T/natural killer (NK) cell function were upregulated, whereas proteins involved in T-cell activation/exhaustion were significantly upregulated in the TCTP-low group. scRNA-seq analyses identified a myeloid subset with high TPT1 (encoding TCTP) expression and TCTP-related molecules, enriched with inhibitory myeloid inflammation gene signatures and providing inhibitory signals to T/NK cells (Macrophage-chemokine). Spatial transcriptomics analyses revealed a tumor-cell-enriched cluster co-localized with the Macrophage-chemokine subset, which exhibited the highest TPT1 expression and a positive correlation between its abundance and average TPT1 levels. In nivolumab-treated patients (cohort 2), the high TCTP group was associated with poor survival outcomes (HR: 1.39 for PFS; 1.47 for OS).Conclusions Plasma TCTP is a prognostic biomarker, reflecting clinically relevant immunosuppressive myeloid signals in patients with gastric cancer.